Trust and justice in the adoption of a welfare e-payment system. Issue 3 (15th August 2016) - Azmi, Anna; Ang, Yen Dee; Talib, Siti Aqilah
Abstract : Purpose: The purpose of this study was to examine the interaction between citizens' perception of justice and their trust in the government agency that provides e-services, in particular, those e-services with users who are particularly sensitive towards their interaction and exchanges with the government. Design/methodology/approach: Analysis of 102 surveys completed by users of e-BR1M was conducted. Partial least squares regression, a form of structural equation modelling, was used for the data analysis. Findings: This study found that distributive justice and procedural justice positively influence trust in government. Trust in government and convenience were also found to significantly influence the adoption of e-BR1M. Research limitations/implications: Understanding the interaction between perceptions of justice (procedural and distributive justice) and trust can contribute to the willingness to adopt e-government services by a particular group of users who are particularly sensitive towards interactions with the government. Practical implications: Findings from this study can help policymakers improve the way in which they interact with citizens so that the citizens' perceptions of procedural and distributive justice are improved. This, in turn, will improve trust in government and will lead to an improved willingness of citizens to use e-government services. Originality/value: This study examined the interaction between citizens' perceptions of trust and justice in an e-government service, which users are particularly sensitive towards in their interactions with the government.